Unhealthy lifestyle may increase later depression via inflammation in older women but not men. (April 2015) - Hiles, Sarah A.; Baker, Amanda L.; de Malmanche, Theo; McEvoy, Mark; Boyle, Michael; Attia, John
Abstract: Depression and inflammatory markers have a reliable cross-sectional association although less is known about the prospective relationship. The current study investigated whether pro-inflammatory markers are prospectively associated with depression, and whether indicators of unhealthy lifestyle, physical health and psychosocial functioning may drive this association. Participants were drawn from the Hunter Community Study, a community-dwelling cohort of individuals aged 55–85 years ( N  = 1410). Participants completed baseline physiological assessment, health-related questionnaires, and blood sampling for the analysis of inflammatory markers, C-reactive protein (CRP) and interleukin (IL)-6. Participants completed the same depressive symptom questionnaire again after 3.5–5.5 years. Depression outcomes at follow-up were analysed dichotomously using established scale cut-off scores and continuously as a "residual score", representing the variation in follow-up depressive symptoms not explained by baseline symptoms and age. Analyses were conducted on males and females separately. At baseline, indicators of unhealthy lifestyle, physical health and psychosocial functioning were associated with depressive symptoms and inflammatory markers. For males, there were no relationships between inflammatory markers and follow-up depression outcomes. In females, IL-6 was significantly associated with depression outcomes in univariate, but not multivariate analyses. However, IL-6 significantly mediated the association between the predictors of waist-to-hip ratio, smoking and psychological coping at baseline, and follow-up depression outcomes. The results support the inflammatory hypothesis of depression, although females may be more vulnerable to effects. The findings raise the possibility that unhealthy lifestyle and psychosocial stress may drive inflammation and subsequent depressive symptoms. Highlights: We note a gender difference in depression-inflammation relationships. Baseline IL-6 predicts future depressive symptoms in women. IL-6 mediates the prospective relationship between adiposity and depression in women. Unhealthy lifestyle may be a source of inflammatory markers in depressed women.